FENOMENA ILUSI FISKAL DALAM KINERJA ANGGARAN PEMERINTAH DAERAH - Adi, Priyo Hardi; Ekaristi, Puspa Dewi (Jurnal Akuntansi dan Keuangan Indonesia, 2009)
This study aimed to find the tendency o f the existence o f fiscal illusion. Local governments do manipulations for not maximizing their own revenue (Pendapatan Asli Daerah) and increasing expenditures in order to get central government transfer (Dana Alokasi Umum) in a larger amount. The result o f this study sho ws the existence of fiscal illusion after the implementation o f local autonomy. Through income measurement analysis, fiscal illusions exist on incomes such as local taxation and indirect taxation. While through expenditure manipulation analysis, fiscal illusions exist on the ratio o f national income which is provided by central government to the local government.